Digital discourse and diplomacy in the context of genocide in Gaza - Maldonado Soto, Jorge (Re-presentaciones: Periodismo, comunicación y sociedad, 2025)
On October 7, 2023, Hamas launched a surprise attack on Israel, intensifying a conflict that has left thousands dead and wounded. On social media, especially on platform X, different views on this situation have clashed. In Chile, Israeli Ambassador Gil Artzyeli has been a controversial figure on that platform, justifying Israeli actions in Palestine, which are considered disproportionate by various states and international and non-governmental organizations. This article analyzes the ambassador's digital discourse on X during the two months before and after the attack, considering his own and shared posts. The study shows that Artzyeli shifted from topics associated with technological innovation to the unconditional defense of Israel's military response in Gaza. Finally, it concludes that social media plays a fundamental role in diplomatic communication in contexts of armed conflict, as it allows for the establishment and defense of official discourse.
Keywords: political communication; digital discourse; social networks; Israel-Hamas conflict; human rights